(untitled) (Palimpsesto, 2024)
The spread of digital devices such as smartphones and Instagram places the body as the administrator of the visibility of its existence. To discuss this premise, high school students (Chile) were invited to participate in the Laboratory of bodily affections, an Instagram profile created to develop an investigation from a digital ethnographic approach in complementarity with interviews and visual analysis of IG publications. From this process we highlight the bodily assemblages with generative technologies - human-non-human bodies that affect (remove) the ways in which bodies are deregulated in digitality.